Strategy to Preserve Srimpi Lobong Dance at Yogyakarta Palace in the Digital Era - Chory Martha; Malarsih Malarsih; Hartono Hartono (Universitas Negeri Medan, 2026)
The Srimpi Lobong dance is one of the classical princess dances that developed in the Yogyakarta Palace environment and has high historical, philosophical and cultural value in Javanese cultural tradition. However, amid the tide of globalisation and digital technology development, the existence of the Srimpi Lobong dance faces various challenges, such as declining interest among the younger generation, limited appreciation space, and shifts in people's cultural consumption patterns. This study aims to examine the philosophical value of the Srimpi Lobong dance, its position in the palace tradition, the preservation challenges it faces, and the preservation strategies implemented in the digital era. This study uses a qualitative approach with a qualitative descriptive method. The data was obtained through observation, in-depth interviews with relevant parties, and documentation in the form of archives, photographs, and videos of performances. The results of the study show that Srimpi Lobong Dance not only functions as a performing art, but also as a medium for passing on ethical values, spirituality, and character education. Preservation strategies include maintaining classical standards, regenerating dancers, and utilising digital media as a means of documentation, promotion, and cultural education. Although digitisation opens up opportunities to broaden appreciation, its use must be selective so as not to lose the philosophical essence and authenticity of classical dance. Thus, the preservation of Srimpi Lobong Dance needs to be understood as a process of sustainable cultural regeneration, which balances the conservation of tradition and adaptation to the times.